Fractional time delay estimation algorithm based on the fractional lower order moment - LIU Wen-hong1; 2; QIU Tian-shuang1; HU Ting-ting1; LUAN Lian-yi3 (Tongxin xuebao)
According to the noise characteristics in signal, a fractional time delay estimation algorithm referred to as LMPFTDE was proposed based on the least mean p-norm. This approach generalized the explicit time delay gain estima-tion （ETDGE） algorithm using the least dispersion criterion. The fractional time delay estimation value could be obtained by minimizing the pth order moment of the error signal. It is shown by theoretical analysis and computer simulations that the proposed method is robust for both Gaussian and non-Gaussian impulsive noise environments.